The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/jo0481250
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Free Palladium-Catalyzed Cyanation of Aryl Halides

Abstract: [reaction: see text] A practical, ligand-free cyanation of aryl bromides that utilizes as little as 0.1 mol % Pd(OAc)(2) in combination with a nontoxic cyanide source, M(4)[Fe(CN)(6)] (M = K, Na), is described. The reactions are performed in DMAC at 120 degrees C and provide the corresponding aryl nitrile in 83-96% yield, typically in less than 5 h. TON values of up to 7100 were attained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(81 citation statements)
references
References 19 publications
1
80
0
Order By: Relevance
“…Among the tested solvents NMP gave comparable results to the standard solvent DMAc (Table 1, entries [13][14][15][16]. Although the use of potassium hexacyanoferrate(II) hydrate was found to be advantageous in some cases, [11,13] in this model reaction a major decrease of the yield occurred (Table 1, entry 19).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Among the tested solvents NMP gave comparable results to the standard solvent DMAc (Table 1, entries [13][14][15][16]. Although the use of potassium hexacyanoferrate(II) hydrate was found to be advantageous in some cases, [11,13] in this model reaction a major decrease of the yield occurred (Table 1, entry 19).…”
Section: Resultsmentioning
confidence: 95%
“…Although the use of potassium hexacyanoferrate(II) hydrate was found to be advantageous in some cases, [11,13] in this model reaction a major decrease of the yield occurred (Table 1, entry 19). Moreover, potassium hexacyanoferrateA C H T U N G T R E N N U N G (III) was tested, but also with low success (Table 1, entry 20).…”
Section: Resultsmentioning
confidence: 97%
“…[12] To prevent catalyst deactivation, a variety of cyanide sources, such as alkali cyanide, zinc cyanide, acetone cyanohydrine, and trimethylsilyl cyanide, in combination with different solvents, have been proposed to fine-tune the cyanide concentration. [13] Recently Beller et al, [14] and subsequently Weissman et al [15] have demonstrated that potassium ferro(ii)cyanide (4) is an excellent cyanide source for the palladium-catalyzed cyanation of aryl halides. Following these observations, an intramolecular Heck-cyanation sequence involving a palladium catalyst was investigated by using o-iodoanilide 5 a as the test substrate with 4 as the terminating agent.…”
Section: Introductionmentioning
confidence: 99%
“…13) Reaction of 4 with pyrrolidine or morpho-line gave the known 4-chloro-5-cycloaminopyridazinones 5a 14) and 5b, 13) respectively. Attempts to directly replace the 4-chloro substituent in compounds of type 5 with a cyano function by palladium-catalyzed cyanation 15) failed, so we decided to introduce the requisite carbon side chain at position C-4 by an electrophilic substitution reaction, after reductive removal of the halogen. Thus, catalytic transfer hydrogenation of 5a, b with ammonium formate/palladium gave the known 5-cycloaminopyridazinones 6a 16) and 6b, 13) respectively.…”
Section: -5)mentioning
confidence: 99%